The Effect of the Fear of COVID-19 on Healthcare Professionals’ Psychological Adjustment Skills: Mediating Role of Experiential Avoidance and Psychological Resilience - Seçer, İsmail; Ulaş, Sümeyye; Karaman-Özlü, Zeynep (Frontiers in Psychology, 2020)
While the COVID-19 outbreak is rapidly spreading all over the world, it has secondary consequences that negatively affect both societies and individuals. The group, which is expected to be exposed to the secondary negative consequences most intensely during the epidemic process and afterwards, is undoubtedly the healthcare professionals. In this research process, the effect of the fear that healthcare professionals developed for the outbreak of COVID-19 on their psychological adjustment skills is examined, and in this context, the mediating role of experiential avoidance and psychological resilience is examined. The research was carried out with a total of 370 healthcare professionals reached via the online data collection method. Structural equation modeling was used in the data analysis process, and the findings obtained were determined that the fear of COVID-19 had a negative effect on the psychological adjustment in healthcare professionals; however, psychological resilience was found to have a protective function that limits this effect, and experiential avoidance has a risk factor that aggravates this effect. Findings obtained from the research are discussed in the context of the literature